Behavioral adaptation to climate change in wildfire‐prone forests. (18th September 2018) - Hamilton, Matthew; Fischer, Alexandra Paige; Guikema, Seth D.; Keppel‐Aleks, Gretchen
Abstract : The link between climate change and increased wildfire risk highlights the need for adaptation in wildfire‐prone landscapes. While extensive research has focused on adaptation at the levels of communities, policies, and governance systems, there is limited understanding of adaptation at the level of individual behavioral responses. Individuals not only directly experience the adverse effects of wildfires but also shape their own exposure to wildfire through risk mitigation practices. Without knowledge of whether these behaviors are adaptive, decision makers are limited in their ability to design and assess climate change adaptation policies that improve outcomes in wildfire‐prone regions. Likewise, greater understanding of the processes by which behavioral adaptation occurs can improve theories of behavior under risk, and specifically how psychological and social factors mediate the effects of hazard conditions on behavior. This paper reviews scholarship on biophysical, psychological, and social factors that shape behavioral adaptation to climate change in wildfire‐prone forests. Our review highlights opportunities to improve theory and assist risk mitigation policy interventions by focusing greater attention on dynamic feedbacks involving hazards, behavior, and outcomes, as well as accounting for variation in behavior and wildfire hazard conditions. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Abstract : The increasing intensity of wildfires highlights the importance of understanding the factors responsible for adaptation of risk mitigation behavior. Credit: U.S. Forest Service.